Japanese Inviting Speech Act Strategy: From Gender Point of View - Chandrawisesa, Galih; Kiyama, Keiko; Haristiani, Nuria; Sudjianto, Sudjianto (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
The invitation acts categorized as an action that is likely to threaten the faceof interlocutors and it is called as face-threatening acts (FTA). There is a need for a strategy in making invitations, so that speakers can maintain their utterance to not interfere the faceof the interlocutors. This study aims to describe the strategies used by Japanese speakers in conducting speech acts to invite friends with similar and opposite gender. The method used in this study is a qualitative descriptive research method. The data was obtained using the discourse completion test (DCT) questionnaire with respondents from 60 Gunma University students (30 men and 30 women). Then, the collected data has been analyzed based on Brown and Levinson’s politeness strategy. Results showed, that in doing invitation speech acts to friends with opposite gender, both male and female speakers tend to use negative politeness strategies. While the positive politeness strategy is only used in small imposition situations and to friends with similar gender. Male speakers tend to use men’s language (danseigo) to similar gender friends, it shows the nature of a man who is strong and full of masculinity. While female speakers use polite and refined language, such as female language characteristics that are more polite and not dominating. From there, it can be seen that Japanese speakers have a high awareness of the differences in the gender of their interlocutor when they do speech acts.